Women's Narratives and the Postmemory of Displacement in Central and Eastern Europe (Palgrave Studies in Life Writing, 2018)
This volume explores the different mechanisms and forms of expression used by women to come to terms with the past, focusing on the variety and complexity of women's narratives of displacement within the context of Central and Eastern Europe. The first part addresses the quest for personal (post)memory from the perspective of the second and third generations. The touching collaboration established in reconstructing individual and family (post)memories offers invaluable insights into the effects of displacement, coping mechanisms, and resilience. Adopting the idea that the text itself becomes a site of (post)memory, the second part of the volume brings into discussion different sites and develops further this topic in relation to the creative process and visual text. The last part questions the past in relation to trauma and identity displacement in the countries where abusive regimes destroyed social bonds and had a lasting impact on the people lives.